The complete mitochondrial genome of black-footed ferret, Mustela nigripes (Mustela, Mustelinae). (3rd May 2016) - Zhao, Ren-Bin; Zhou, Chao-Yang; Lu, Zhi-Xiang; Hu, Peng; Liu, Jian-Qiong; Tan, Wei-Wei; Yang, Tong-Hua
Abstract: In this study, the complete mitochondrial genome sequence of black-footed ferret, Mustela nigripes, is determined for the first time. This mitogenome is 16, 556 bp in length and contains 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 1 control region (D-loop). The overall base composition is A (32.9%), C (26.1%), G (13.8%), and T (27.2%), so the percentage of A and T (60.1%) is higher than that of G and C. Most of the genes are encoded on H-strand, except for the ND6 subunit gene and six tRNA genes. The complete mitochondrial genome sequence reported here would be useful for further phylogenetic analysis and conservation genetic studies in M. nigripes.